Gps Satellite Orbit Integration by the Gauss-Jackson Process - Sharif, Ayob (Fakulti Ukur dan Harta Tanah, 1992)
High precision orbit determination Is a key requirement In preslce relative and absolute positioning by the Global Positioning System (OPS) The Gauss-Jackson 8^ Order Process using the predictor corrector scheme is used in the study to perform the orbit integration. The mathematical expressions, accuracy and efficiency of the method are discussed Results show that the Gauss-Jackson numerical procedure proved to be a precise and efficient method for the GPS orbit determination.